Monitoring of Outdoor and Indoor Air Particulate Matter (PM10) at Buildings Located in An Industrial District - Al-Sahari, Mohammed; Adel Al-Gheethi,; Zaidah, Siti; Saphira, Radin Maya; Al Madhoun, Wesam; Anaam, Ahmed Abdulmalek (International Journal of Sustainable Construction Engineering and Technology, 2023)
Particulate matter (PM10) pollution has become a problem of significant impact in many countries and cities due to its dangerous effects on public health and environmental balance. The current study aims to monitor the indoor and outdoor PM10 concentrations of the buildings located next to an industrial area that releasing industrial fumes. Three buildings were selected to be investigated. Two factors were considered in the current study, including the outdoor PM10 and wind speed. Response surface methodology (RSM) design was used to identify the relationship between the outdoor and indoor PM10 concentration (I/O) through the ANOVA analysis (P